Metal-Based Drug–DNA Interactions and Analytical Determination Methods - Adriana Corina Hangan; Luminița Simona Oprean; Lucia Dican; Lucia Maria Procopciuc; Bogdan Sevastre; Roxana Liana Lucaciu (Molecules)
DNA structure has many potential places where endogenous compounds and xenobiotics can bind. Therefore, xenobiotics bind along the sites of the nucleic acid with the aim of changing its structure, its genetic message, and, implicitly, its functions. Currently, there are several mechanisms known to be involved in DNA binding. These mechanisms are covalent and non-covalent interactions. The covalent interaction or metal base coordination is an irreversible binding and it is represented by an intra-/interstrand cross-link. The non-covalent interaction is generally a reversible binding and it is represented by intercalation between DNA base pairs, insertion, major and/or minor groove binding, and electrostatic interactions with the sugar phosphate DNA backbone. In the present review, we focus on the types of DNA–metal complex interactions (including some representative examples) and on presenting the methods currently used to study them.